The Preventive Effect of Dopamine Infusion in Rats with Abdominal Compartment Syndrome - SARAÇOĞLU, AYTEN; UĞURLU, MUSTAFA ÜMİT; UMUROĞLU, TÜMAY (TAYLOR & FRANCIS INC, 2013)
Background: The most significant perfusion disorder of the intra-abdominal viscera occurs in the abdominal compartment syndrome (ACS). Free oxygen radicals diffuse into the body during the reperfusion phase of ACS. Our aim was to determine the effects of dopamine infusion (3 mu g/kg/min) on renal perfusion, cytokine levels, free oxygen radicals, and renal histopathological changes in the presence of ACS in a prospective randomized manner. Methods: Twenty-four male Sprague-Dawley rats were randomly divided into four groups (n = 6). Group 1 was used as control. In group 2, air was inflated until the intra-abdominal pressure (IAP) reached 20 mmHg. In group 3, dopamine was infused for 60 min meanwhile IAP was kept at 20 mmHg. In group 4, dopamine was infused for 60 min before IAP rise. After this phase, renal artery (RA) perfusion was measured continuously. Myeloperoxidase activity (MPO), glutathione (GSH), and lipid peroxidation (MDA) levels were measured in tissue samples and histopathological scoring was performed. Results: Dopamine treatment before and during ACS significantly decreased MPO and MDA levels and also increased renal blood flow and GSH levels. However, histopathological damage was improved simultaneously. Conclusion: Dopamine infusion before and during ACS, increases renal perfusion and decreases free oxygen radicals. According to our findings, dopamine infusion may be proposed for the treatment of ACS and perfusion disorders in critically ill patients.
Keywords: dopamine; abdominal compartment syndrome; renal artery; intra-abdominal hypertension; ischemia reperfusion; injury; BLOOD-FLOW; RESPONSES; PROTECTS